Surface-displayed silicatein-α enzyme in bioengineered E. coli enables biocementation and silica mineralization - Vigil, Toriana N.; Schwendeman, Nikolas K.; Grogger, Melanie L. M.; Morrison, Victoria L.; Warner, Margaret C.; Bone, Nathaniel B.; Vance, Morgan T.; Morris, David C.; McElmurry, Kristi; Berger, Bryan W.; Steel, J. Jordan (Frontiers in Systems Biology, 2024)
Biocementation is an exciting biomanufacturing alternative to common cement, which is a significant contributor of CO2 greenhouse gas production. In nature biocementation processes are usually modulated via ureolytic microbes, such as Sporosarcina pasteurii, precipitating calcium carbonate to cement particles together, but these ureolytic reactions also produce ammonium and carbonate byproducts, which may have detrimental effects on the environment. As an alternative approach, this work examines biosilicification via surface-displayed silicatein-α in bio-engineered E. coli as an in vivo biocementation strategy. The surface-display of silicatein-α with ice nucleation protein is a novel protein fusion combination that effectively enables biosilicification, which is the polymerization of silica species in solution, from the surface of E. coli bacterial cells. Biosilicification with silicatein-α produces biocementation products with comparable compressive strength as S. pasteurii. This biosilicification approach takes advantage of the high silica content found naturally in sand and does not produce the ammonium and carbonate byproducts of ureolytic bacteria, making this a more environmentally friendly biocementation strategy.